Analisis Beban Kerja Mental Menggunakan Metode NASA-TLX pada Engineering Departement (Studi Kasus PT. Muliaglass Float Division) - Alfianto, Rafly; Azizah, Fahriza Nurul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT Muliaglass Float Division, a subsidiary of PT Mulia Industrindo, operates in the glass and ceramic industry with a large production capacity every day. Therefore, it is necessary to analyze the extent of psychological stress and what factors affect it. One way to measure mental workload is NASA-TLX. The National Aeronautics and Space Administration Task Load Index (NASA-TLX) is used to assess emotional mental load. The NASA TLX method is a mental workload measurement method that measures workload by dividing it into six aspects of work elements. NASA-TLX is divided into two phases. That is, comparing each scale and rating job performance. A total of 20 employees of the Engineering Department will be included in the study by distributing questionnaires. The results of the research calculations show an average Weight Work Load (WWL) score of 62.67 which falls into the high category. Further evaluation revealed influencing variables, including lack of rest time, lack of work office, and lack of inspiration at work that affect employee performance.